Treatments and Therapies for Speech Delay Children: A LITERARY STUDY - Munawwir Hadiwijaya; Maya Rizki Amalyasari (ANFA MEDIATAMA, 2022)
Treatment for speech delay typically involves working with a speech-language pathologist (SLP) to develop an individualized plan for the child. The treatment plan will depend on the type and severity of the speech delay and may involve a combination of different approaches, such as: Articulation therapy, Language intervention therapy, Oral motor therapy, Augmentative and alternative communication (AAC), and Play-based therapy. In addition to working with an SLP, parents can also play an important role in the treatment of speech delay by practicing speech and language activities at home with their child. It's important to work closely with the SLP to ensure that the child receives appropriate and effective treatment for their specific needs.